Catalytic hydrogen generation from sodium borohydride using Ni foam supported Fe-B - Ocon, Joey D. (2011.)
In this study, Fe-B catalysts were coated on the Ni foam through chemical reduction of FeCI³ and NaBH⁴ precursors. The catalytic properties of Fe-B, catalytic loading on the Ni foam and hydrogen generation rates in water were found to be sensitive to the preparation conditions including concentrations of precursors, pH and the number of dip-coating cycles. Catalytic activities of the synthesized catalyts to hydrogen production were examined in a batch reactor with a gas flow meter to measure the generation rates. The surface morphologies of the as-prepared catalysts were studied using Scanning Electron Microscopy (SEM). The crystal structure and the presence of the Fe-B catalyst in the catalyst support's surface were investigated using X-ray diffraction (XRD). The XRD pattern of the precipitate in the Ni foam showed a board diffraction peak around 57.65̊C which is assigned to the (001) diffraction of Fe-B. High catalytic activity of the Fe-B catalyst was obtained with the following preparation conditions. 15 wt. % FeCI₃, 15 wt. % NaBH₄, 1 wt. % NaOH, fifteen dipping cycles and drying the catalyst for 2.0 hours at 60̊̊C. The effect of the water-methanol mixture ratios on the kinetics of hydrolysis of sodium borohyride in the presence of Fe-B catalyst was investigated. High hydrogen generation rates were obeserved as the methanol concentrations increased. Kinetic studies showing pseudo-first order rate kinetics with respect to sodium borohydride concentration for pure methanol was confirmed in this study. Activation energy (7.02 kJ/mol) of the catalytic methanolysis was lower when compared with activation energies of catalytic and non-catalytic hydrolysis found in literature. A gradual decline in the catalytic activity was observed for repeated runs in water and methanol. Finally, supported Fe-B/Ni can be a good candidate for cheap but highly active catalyst for hydrogen generation in sodium borohydride.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Sodium borohydride; Iron catalysts; Nickel catalysts; Catalytic hydrolosis